2006
DOI: 10.1111/j.1472-765x.2005.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effect of acridine orange on the expression of penicillin G acylase and beta-lactamase in Escherichia coli

Abstract: Aims:  The present work aimed to improve the production of penicillin G acylase (PGA) and reduce the β‐lactamase activity through acridine orange (AO) induced mutation in Escherichia coli. Methods and Results:  Three wild E. coli strains BDCS‐N‐FMu10, BDCS‐N‐S21 and BDCS‐N‐W50, producing both the enzymes PGA and β‐lactamase were treated by AO. Minimum inhibitory concentration of AO was 10 μg ml−1 and it was noted that bacterial growth was gradually suppressed by increasing the concentration of AO from 10 to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Although excellent image quality can be achieved with the CME using nuclear stains, there is concern about the cytotoxicity and potential mutagenicity of these materials. These dyes have been shown to cause damage to DNA (Epe et al , 1993) and to be mutagenic (Arshad et al , 2006) to cells in culture. A clinical trial has indicated that AO used in conjunction with radiation therapy can help in the treatment of synovial sarcomas in humans (Kusuzaki et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although excellent image quality can be achieved with the CME using nuclear stains, there is concern about the cytotoxicity and potential mutagenicity of these materials. These dyes have been shown to cause damage to DNA (Epe et al , 1993) and to be mutagenic (Arshad et al , 2006) to cells in culture. A clinical trial has indicated that AO used in conjunction with radiation therapy can help in the treatment of synovial sarcomas in humans (Kusuzaki et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another mutant strain BDCS-N-W50 M40 retained from the same parent (BDCS-N-W50) supported higher PGA yield (20.6 mg 6-APA h −1 mg −1 wet cells) with the functional inactivation of β-lactamase. In a previous study, PGA production by an acridine orange (AO)-treated mutant derivative was improved two-fold over its parental E. coli strains (Arshad et al 2006b). Comparison of these chemical mutagens shows that MNNG is a more potent chemical mutagen that can increase the mutation frequency and PGA yield in E. coli strains.…”
Section: Discussionmentioning
confidence: 96%
“…A small number of cells (1×10 3 ) from the diluted culture were inoculated into bulk culture and ten parallel cultures were inoculated per strain. The cultures were incubated overnight at 37°C, and 10μL from each culture was then plated on selective media for mutant colonies producing PGA-or β-lactamase, respectively (Arshad et al 2006b). The total number of viable cells was determined by plating 10 −6 dilution of bulk culture and pooled parallel cultures on non-selective medium.…”
Section: Luria-delbruck Fluctuation Assaymentioning
confidence: 99%
See 2 more Smart Citations